Carrie (1976) [videorecording (DVD)] - De Palma, Brian; Spacek, Sissy; Travolta, John, 1954-; Laurie, Piper, 1932-; King, Stephen, 1947- (MGM Home Entertainment, 2001)
"Carrie White is a shy young girl who doesn't make friends easily. After her classmates taunt her about her horrified reaction to her totally unexpected first period one of them takes pity on her and gets Tommy Ross, her boyfriend and class hunk to invite Carrie to the senior prom. Meanwhile another girl who has been banned from the prom for her continued aggressive behaviour is not as forgiving and plans a trick to embarrass Carrie in front of the whole school. What she doesn't realise is that Carrie is-- gifted, and you really don't want to get her angry"--Internet Movie Database.